The Effect of Health Education on Knowledge and Attitude in First Aid Food Poisoning in Students of SD N 1 Kutasari - Fatmawati, Eva; Fitriana, Nurul Fatwati (Proceedings Series on Health & Medical Sciences, 2022)
Poisoning is an emergency caused by the entry of a harmful substance or food into the body in various ways.This research aimed to figure out the effect of health education about the first aid for food poisoning on the knowledge and attitude of students at SD N 1 Kutasari. This was pre-experimental quantitative research using a one group pretest-posttest research design. Based on the Wilcoxon test results, the significance value was 0.001 (p0.05), while based on the Paired T-test results was 0.000 (p0.05). There is an effect of health education on the knowledge and attitude of students for the first aid for food poisoning at SD N 1 Kutasari